Analisis Pengaruh Desain Pembelajaran Berbasis Teknologi Informasi dan Persepsi Guru terhadap Hasil Belajar Sejarah Kebudayaan Islam Siswa Madrasah Tsanawiyah Islam Terpadu Bogor - kartika, ika; Fabianza, Iqbal; Sunasa, Arman Aria (EduInovasi: Journal of Basic Educational Studies, 2024)
This article attempts to analyze the influence of information technology-based learning design and teacher perceptions on Islamic Cultural History learning outcomes. Judging from the results of the documentation of the teachers' Learning Implementation Plan (RPP) at the Bogor Integrated Islamic Tsanawiyah Madrasah, it is in accordance with the RPP format of the independent curriculum. Learning by utilizing ICT is an urgent need and a demand to increase the effectiveness of the Islamic Religious Education learning process. Through learning interactions that utilize the internet network, the potential for creating more effective learning in the subject of Islamic Cultural History can be realized. The aim of this research is to analyze the influence of information technology-based learning and teacher perceptions on the learning outcomes of the history of Islamic culture at the Bogor Integrated Islamic Tsanawiyah Madrasah for the 2022-2023 academic year. This research uses a quantitative research design with the SEM method and Smart-PLS approach. Calculation results using Smart-PLS software explain the data results based on assessment questionnaire data. The goodness value of the R-Square model from the SEM calculation is that the Islamic Cultural History Learning Outcome has a value of 0.725. In the F-Square section, Learning Design has a value of 1.401 while Teacher Perception has a value of 0.015.